Melanotan-induced priapism: a hard-earned tan. Issue 2 (21st February 2019) - Dreyer, Barend Albert; Amer, Tarik; Fraser, Michael
Abstract : Melanocortin analogues, such as melanotan, are illegally used for artificial tanning. They have also been suggested as possible therapeutic agents in the treatment of erectile dysfunction. This case study presents a patient attending the accident and emergency department, in a tertiary urology centre, with acute priapism after abdominal subcutaneous injection of melanotan. The priapism was diagnosed as 'low-flow' and managed with cavernosal aspiration, irrigation and subsequent intracavernosal injection of phenylephrine. The patient avoided requiring surgical shunting but had not yet recovered erectile function at 4-week follow-up. Acute priapism is an unreported side effect of melanocortin analogue use and this case report presents a patient managed without surgical intervention. Future therapeutic application of these agents will need to take this potential life altering complication into consideration.